2010
DOI: 10.1371/journal.pone.0008524
|View full text |Cite
|
Sign up to set email alerts
|

Echinocandin Treatment of Pneumocystis Pneumonia in Rodent Models Depletes Cysts Leaving Trophic Burdens That Cannot Transmit the Infection

Abstract: Fungi in the genus Pneumocystis cause pneumonia (PCP) in hosts with debilitated immune systems and are emerging as co-morbidity factors associated with chronic diseases such as COPD. Limited therapeutic choices and poor understanding of the life cycle are a result of the inability of these fungi to grow outside the mammalian lung. Within the alveolar lumen, Pneumocystis spp., appear to have a bi-phasic life cycle consisting of an asexual phase characterized by binary fission of trophic forms and a sexual cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
170
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(186 citation statements)
references
References 46 publications
(64 reference statements)
12
170
2
2
Order By: Relevance
“…It has long been held that the periplasmic space in the ascus was the repository for glucan, as that space increases throughout maturation. However, staining with a monoclonal antibody (MAb) to ␤-glucan suggests it may be on the surface of the asci as well, which is in keeping with the recognition of these forms via Dectin-1 (7).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…It has long been held that the periplasmic space in the ascus was the repository for glucan, as that space increases throughout maturation. However, staining with a monoclonal antibody (MAb) to ␤-glucan suggests it may be on the surface of the asci as well, which is in keeping with the recognition of these forms via Dectin-1 (7).…”
mentioning
confidence: 72%
“…We have shown that treatment of Pneumocystis-infected mice and rats with inhibitors of ␤-glucan synthesis, the echinocandins, dramatically shifted the mixed ascus and trophic form populations to ones made almost exclusively of trophic forms (7). The mortality was markedly reduced in the mice treated with echinocandins, especially anidulafungin, yet large populations of trophic forms were present in their lungs.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…To accomplish this, we employed the rat Pc pneumonia model that has been used extensively to analyze drug activity against the organism (6,60,61). Due to limited drug supply, we treated the rats with nikkomycin Z by oral gavage after establishment of fulminate PCP by immune suppressing rats with corticosteroids and inoculating with Pc.…”
Section: Efficacy Of the Inhibitor Nikkomycin Z In The Rat Model Ofmentioning
confidence: 99%
“…We and others have shown that the Pneumocystis species contain b-glucan synthetases that can be inhibited by specific b-glucan inhibitors, such as the echinocandins, pneumocandins, and newly generated compounds (3,4,6,7). A number of these drugs are already implemented as antifungal therapies against pathogens (8).…”
mentioning
confidence: 99%